Characterization of SCOBY and Lactiplantibacillus plantarum ELB90 Fermented Coffee Kombucha from Different Coffee Sources - Saroglu, Oznur; Irmak, Yagmur Gulce; Yildirim, Rusen Metin; Karadag, Ayse (MDPI, 2025)
Coffee kombucha beverages were developed by fermenting various coffee substrates, including instant coffee (I), coffee brews of ground coffee beans (G), and additional spent coffee added ground coffee (GSC) using either SCOBY (S) or Lactiplantibacillus plantarum ELB90 (L), or a combination of both (SL). The combined SL inoculation did not synergistically enhance the growth of acetic and lactic acid bacteria, nor did it increase the acetic and lactic acid concentrations or improve retention of caffeoylquinic acids (CQA) compared to non-fermented controls stored for the incubation period (7 days). Samples fermented with L better preserved the total CQAs during incubation, notably increasing 3-CQA and 4-CQA in L-fermented G and GSC samples by up to 40%, whereas 5-CQA showed a slight decrease (up to 8%) in L-fermented G and GSC samples. After one week, all fermented samples maintained stable levels of 3-CQA compared to the non-fermented SCG control, with significantly elevated 4-CQA. Caffeic acid was detected only in the bound fraction of beans, exhibiting similar concentrations in both fermented and non-fermented samples. SL-fermented coffees showed significant reductions in caffeine contents, except for I coffee substrate, and spent coffee grounds (SCG) filtered from the SL-fermented sample also had significantly lower caffeine content. Panelists preferred coffee kombucha beverages inoculated with S over those fermented with L, which were rated least appealing. The study concludes that fermentation with specific inoculation cultures could mitigate the degradation of coffee phenolic compounds during storage and facilitate the production of beverages with lower caffeine content, potentially enhancing both functional properties and consumer acceptability.
Keywords: SCOBY; spent coffee grounds; caffeine; chlorogenic acid; acetic acid bacteria; LACTIC-ACID BACTERIA; PHENOLIC-COMPOUNDS; FUNCTIONAL-PROPERTIES; ANTIOXIDANT ACTIVITY; TEA; POLYPHENOLS; MELANOIDINS; Biotechnology & Applied Microbiology; Food Science & Technology